Therapeutic efficacy and safety of Kangfuxin in combination with rabeprazole in the treatment of peptic ulcer: A systematic review and meta-analysis. Issue 48 (25th November 2020) - Lin, Meisi; Zhang, Siyuan; Zhang, Minyue; Shi, Jinfeng; Zhang, Chen; Luo, Ruifeng; You, Jieshu; Sun, Jiayi; Zhang, Jinming; Gao, Fei
Abstract: Background: Kangfuxin (KFX), a well-known Chinese patent medicine which extracted from Periplaneta americana, is widely used as an adjuvant in the treatment of peptic ulcers (PUs) with proton pump inhibitors (PPIs) such as rabeprazole, in China. However, no clear consensus has been reached on the efficacy for PU treatment. Methods: We searched in 7 electronic databases to find randomized controlled trials (RCTs) completed before May 31, 2020 to explore the clinical efficiency of KFX plus rabeprazole in the treatment of PU. Risk ratio (RR) corresponding to 95% confidence interval (CI) was calculated to estimate the outcomes. Publication bias was assessed by both Egger's and Begg's tests. Statistical analyses were performed using RevMan 5.4 and Stata version 10.0. Results: Twenty-five RCTs, comprising 2555 PU patients, were included in this study. Meta-analysis showed that, when compared with rabeprazole-based treatment alone, KFX plus rabeprazole significantly improved the healing rate (RR = 1.34, 95% CI 1.25–1.44) and overall response rate of ulcers (RR = 1.16, 95% CI 1.13–1.20), alleviated the clinical symptoms of PU (RR = 1.14, 95% CI 1.08–1.21), and reduced the recurrence of PU (RR = 0.38, 95% CI 0.24–0.61) without an increase in the occurrence of adverse events (RR = 0.92, 95% CI 0.66–1.28). Conclusion: Our study suggests that KFX combined with rabeprazole showed positive therapeutic effects and is safe for treating PU, which may provide more reliable evidence for the clinical use of KFX in the treatment of PU. Abstract : Supplemental Digital Content is available in the text